Pengaruh Tingkat Pendapatan Tenaga Kerja Indonesia terhadap Kelangsungan Pendidikan Anak di Dusun Ceret Desa TKI (Jenggik Utara) - Suhaili Munahar (FONDATIA, 2018)
This study aims to determine the effect of income levels of TKI to the continuity of education of Children in Ceret Village TKI (North Jenggik). The subject of this study is the parents of students in the village of Ceret, especially families who become migrant workers with a sample of KK people from a population of 150 families. Data collection using Questionnaire in the form of income level, while documentation in the form of data of Villagers and School. The research method that will be used is quantitative descriptive research with correlational approach. While the data collection method used is the questionnaire method and documentation method. Data obtained through data collection was analyzed by statistic method with the formula of product moment rent as follows: From r test value above, where r observation equal to 0,9819 smaller than r table equal to 0,991 With significance level 5% then r is significant. So the conclusions of the analysis of this study are: "There is Influence of the level of income of Indonesian labor on the sustainability of children's education in the village of Ceret North Jenggik Village Kec. Montong Gading Kab. East Lombok Year 2017.